Problematika Profesi Tenaga Pendidik di Indonesia antara Idealitas dan Realitas - Desti Arianti; Rahmawati; Rina Zakiah; Khasbi Ainun Najib (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This article discusses the problems faced by educators in Indonesia, with a special emphasis on the situation at SDN Wonorejo. Although the ideal of the teaching profession is expected to create an ideal learning environment, various problems such as high workload, low welfare levels, and lack of supporting facilities often hinder this achievement. In this study, a qualitative approach was used to study the experiences and perspectives of teachers at SDN Wonorejo through interviews and observations. The results showed that there was a difference between what educators expected and what actually happened. They also showed how important the role of the government and their assistance was.